The Social Cost of the Republic: Defense System Workers in Cartagena de Indias, 1750-1850 - Solano D., Sergio Paolo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In order to determine the social consequences of the Independence movement on the free working population of Cartagena de Indias, this paper compares the economic investments and amount of workers hired in the defense systems of this city between 1750 and 1850, focusing on the years of Independence as turning point. Current historiographical debates on the consequences that Independence movements had on the Hispanic American economies and societies serve as backdrop for this study, which poses that the combination of loss of privileges, changes in political situation and international war strategies, together with the budget crisis of the growing Republic, affected labor demand in this city and its defense systems.